Kepemimpinan dan Peningkatan Mutu Pendidikan di Pesantren - Abd Aziz; Poppy Rachman (LP3M Institut Ilmu Keislaman Zainul Hasan, 2021)
This paper aims to review the leadership and improvement of education quality in islamic boarding school. To realize the objectives of boarding school, a leader who has the ability to answer various challenges, have a vision to be come the excellent boarding school, and the effort to achieve it with high energy and commitment. Leaders who always try to influence their subordinates through direct communication by emphasizing the importance of values, assumptions, commitments, and beliefs and have a determination to achieve the goals. Leaders act in way to motivate and inspire subordinates through the giving of meaning and challange to the duties of subordinates. The meaning of the quality of education is the suitability of the needs in education which one means to improve the quality of human resouces as well as to produce changing of human to become a perfect human beings with the noble character and good personality.